2015
DOI: 10.1021/acsnano.5b05468
|View full text |Cite
|
Sign up to set email alerts
|

Nanotube Electromechanics beyond Carbon: The Case of WS2

Abstract: The incorporation of nanostructures into nanoelectronic and nanoelectromechanical systems is a long sought-after goal. In the present article, we report the first torsional electromechanical measurements of pure inorganic nanotubes. The WS2 nanotubes exhibited a complex and reproducible electrical response to mechanical deformation. We combined these measurements with density-functional-tight-binding calculations to understand the interplay between mechanical deformation, specifically torsion and tension, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 61 publications
9
33
0
Order By: Relevance
“…By analyzing the stress-strain/conductivities relationship of samples 8-11, it was found that the DC current increased (electrical resistance decrease) upon increasing the stress in the samples (Figure 9(b)). It was shown before that by applying tensile force on individual WS 2 nanotube using nanoelectromechanical devices a current increase is expected [26]. These results are also in agreement with theoretical study where structural modifications of the WS 2 nanotube and lowering of its bandgap are predicted due to the W-S nanotube bond elongation (and angular distortion) through the tensile stress [24].…”
Section: Journal Of Nanomaterialssupporting
confidence: 88%
See 2 more Smart Citations
“…By analyzing the stress-strain/conductivities relationship of samples 8-11, it was found that the DC current increased (electrical resistance decrease) upon increasing the stress in the samples (Figure 9(b)). It was shown before that by applying tensile force on individual WS 2 nanotube using nanoelectromechanical devices a current increase is expected [26]. These results are also in agreement with theoretical study where structural modifications of the WS 2 nanotube and lowering of its bandgap are predicted due to the W-S nanotube bond elongation (and angular distortion) through the tensile stress [24].…”
Section: Journal Of Nanomaterialssupporting
confidence: 88%
“…The semiconducting properties of individual WS 2 nanotubes were also investigated [24][25][26]. Inorganic nanotubes of WS 2 (INT-WS 2 ) showed a high conductivity (in vacuum conditions) [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24,25] In contrast to the highly intensive research on CNT-based gas sensors; [26] to our best knowledge,MoS 2 and WS 2 nanotubes were not testedf or such ap urpose. At heoretical study of NO, NO 2 ,C O, SO 2 ,a nd NH 3 adsorption on singlewalled NT-MoS 2 was reported recently, [27] however sensing applications of molybdenuma nd tungsten disulfide nanotubes are still limitedt os tress monitoring of structuralc omponents, [28] and nanometric motion sensors [29] employing NT-WS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic layered materials can form fullerene-like nanoparticles (IF) and nanotubes (INT) that exhibit remarkable mechanical, 1,2 optical, 3 and electronic 4,5 properties. Gallium sul¯de (GaS) (P63/ mmc space group) is one such layered compound.…”
Section: Introductionmentioning
confidence: 99%